Integrating PhET Interactive Simulations to Enhance Students' Mathematical Understanding and Engagement in Learning Mixed Fractions - Slamet Arifin; Fazilah binti Razali; Winanjar Rahayu (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
This study aims to document how the integration of PhET interactive simulations into mathematics learning enhances students' conceptual understanding of mixed fractions. This collaborative action research project adhered to the action research cycle proposed by Kemmis and McTaggart. In total 17 4th-grade students from one of the public elementary schools in Malang City, Indonesia participated in this investigation. The data was collected through tests, interviews, and classroom observation. The test of students' mathematical understanding (TSMU) was administered to the students at the pre-cycle, post-cycle I, and post-cycle II stages. The number of questions given in each test was 10 mathematical problems, and they were designed to assess students' mathematical understanding of mixed fractions. The quantitative data was analyzed by using descriptive statistics using SPSS 25, and the qualitative data was analyzed simultaneously using a qualitative data analysis cycle. The research findings unveiled the following key insights. First, we found a notable enhancement in students' mathematical understanding of mixed fractions emerged throughout the study. Specifically, the pre-cycle average score for students' mathematical understanding stood at M=51.59, which saw substantial improvement in the post-cycle I phase (M=61.53) and further growth in the post-cycle II phase (M=76.94). Moreover, the utilization of PhET simulations was found to significantly enhance students' engagement in the realm of mathematics learning. Therefore, the integration of PhET interactive simulations in mathematics learning has been shown to have a significant effect on improving students' mathematical understanding and engagement in learning fraction.